An Analysis of Metaphor in Keshi’s Album ‘Requiem’ - Vahendra , Muhammad Dzacky; Djalius, Yusmarni (LingoLitera, 2026)
This study examines how Keshi uses metaphors in his album Requiem to express emotions and convey deeper meanings in his lyrics. By analyzing the songs through the lens of Lakoff and Johnson’s Conceptual Metaphor Theory, the research identifies the types of metaphors used and explores what they mean in the context of each song. This study applies Use Theory by Wittgenstein to interpret the meanings of metaphors found in the song lyrics. Using a qualitative approach, the study focuses on three categories of metaphors: Orientational, Ontological, and Structural, to see how they shape the listener’s understanding of the themes and emotions Keshi expresses. The analysis of these metaphorical expressions shows that metaphors play a significant role in shaping the meaning of the lyrics, providing a framework for understanding the feelings and emotions expressed by the singer. This article presents one representative metaphor from each song, selected for its clarity and relevance to the metaphor type. The findings show that metaphorical expressions significantly contribute to the depth and emotional resonance of Keshi’s lyrics.